1996
DOI: 10.1016/s0035-9203(96)90315-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical profiles of acute invasive diarrhoea with special reference to mucoid episodes: a rural community-based longitudinal study

Abstract: A study was carried out in 3 villages near Calcutta, India, having a population of 5464, between August 1992 and December 1994. A cohort of rural children below 4 years of age was prospectively observed to determine the clinico-epidemiological aspects of mucoid diarrhoea and examine propensity to invasiveness. Overall, the incidence of diarrhoea was 1.7 episodes/child/year, and that of mucoid and bloody dysentery was 0.8 and 0.2 episodes/child/year, respectively. Children aged 6-11 months had a higher incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…In this study, diarrhea was defined by the passing of three or more loose stools in a 24-hour period as detected by the mother or the responsible caregiver, similar to what has been suggested by the WHO [12] and adopted in many studies [13][14][15][16][17][18][19][20], but contrasting to others who have defined diarrhea as at least four dejections per day [21][22][23] or according to parental definition [10,[24][25][26]. Most recent studies consider that the passing of three or more unformed stools or any number with the presence of blood over a 24-hour period define diarrhea satisfactorily on adults and children older than two years, while to define an episode of diarrhea, the illness has to be preceded and followed by at least three days free of diarrhea [6,13,14,[27][28][29].…”
Section: Discussionsupporting
confidence: 71%
“…In this study, diarrhea was defined by the passing of three or more loose stools in a 24-hour period as detected by the mother or the responsible caregiver, similar to what has been suggested by the WHO [12] and adopted in many studies [13][14][15][16][17][18][19][20], but contrasting to others who have defined diarrhea as at least four dejections per day [21][22][23] or according to parental definition [10,[24][25][26]. Most recent studies consider that the passing of three or more unformed stools or any number with the presence of blood over a 24-hour period define diarrhea satisfactorily on adults and children older than two years, while to define an episode of diarrhea, the illness has to be preceded and followed by at least three days free of diarrhea [6,13,14,[27][28][29].…”
Section: Discussionsupporting
confidence: 71%
“…The systematic literature search yielded 5708 titles for children (Figure 1), of which we identified 41 and 27 studies for inclusion in the analysis of duration [8-48] and severity [8,9,16,19,21,22,25,26,36,39,43,45,49-63], respectively. All included studies reported data on children 0-59 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…This method differs from other studies which collected data on home visits once in a month [21,22], fortnightly [15,20], and once [4,8,14], twice [23][24][25] or three times [26,27] in a week. To our knowledge, the study from Haque et al [12] is the only one with the same methodology to ours published to date.…”
Section: Discussionmentioning
confidence: 99%